Bam and Bgcn antagonize Nanos-dependent germ-line stem cell maintenance. - Li, Y.; Minor, N.T.; Park, J.K.; McKearin, D.M.; Maines, J.Z. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
The balance between germ-line stem cell (GSC) self-renewal and differentiation in Drosophila ovaries is mediated by the antagonistic relationship between the Nanos (Nos)-Pumilio translational repressor complex, which promotes GSC self-renewal, and expression of Bam, a key differentiation factor. Here, we find that Bam and Nos proteins are expressed in reciprocal patterns in young germ cells. Repression of Nos in Bam-expressing cells depends on sequences in the nos 3'-UTR, suggesting that Nos is regulated by translational repression. Ectopic Bam causes differentiation of GSCs, and this activity depends on the endogenous nos 3'-UTR sequence. Previous evidence showed that Bgcn is an obligate factor for the ability of Bam to drive differentiation, and we now report that Bam forms a complex with Bgcn, a protein related to the RNA-interacting DExH-box polypeptides. Together, these observations suggest that Bam-Bgcn act together to antagonize Nos expression; thus, derepressing cystoblast-promoting factors. These findings emphasize the importance of translational repression in balancing stem cell self-renewal and differentiation.